The Ambiguity of Copyright Law in Photography Based on Artificial Intelligence within the Radburch Formula Framework - Yamani Naufal (Jurist-Diction, 2026)
The development of artificial intelligence (AI) technology has presented new challenges in the copyright law regime. One of these challenges is the emergence of photographic works that are produced entirely or partially by AI. The main issues that arise are who can be categorized as the creator, whether the work meets the elements of originality, and how AI-based creations are protected by law. In the Indonesian context, Law No. 28 of 2014 on Copyright does not explicitly regulate the position of AI works, thus creating legal uncertainty. This study uses a normative legal method with a conceptual approach. The results of the analysis show that there is a normative gap regarding the legal subject in AI creations, as well as a debate regarding the requirements for originality. Therefore, regulatory reconstruction is needed, either by expanding the definition of creator or through a specific attribution model, so that legal protection can reflect the principles of certainty, fairness, and benefit.